Main Features and Control Strategies to Reduce Overcrowding in Emergency Departments: A Systematic Review of the Literature - Maninchedda M; Proia AS; Bianco L; Aromatario M; Orsi GB; Napoli C (Dove Medical Press, 2023)
Mario Maninchedda,1 Anna Silvia Proia,1 Lavinia Bianco,1 Mariarosaria Aromatario,2 Giovanni Battista Orsi,1,2 Christian Napoli2,3 1Department of Public Health and Infectious Diseases, "Sapienza" University of Rome, Rome, Italy; 2Sant' Andrea University Hospital, Rome, Italy; 3Department of Medical Surgical Sciences and Translational Medicine, "Sapienza" University of Rome, Rome, ItalyCorrespondence: Christian Napoli, Email christian.napoli@uniroma1.itPurpose: Overcrowding is a problem that affects emergency departments (ED) all over the world; it occurs due to a disproportion between user demand and the physical, human and structural resources available. Essential prerequisites to assessing and managing the phenomenon are its accurate measurement and an understanding of its impact. The objective of this systematic review is to identify the characteristics of the problem, analyzing the proposed strategies aimed at improving patient flow, delay in services provided and overcrowding of emergency departments.Methods: To achieve our objectives, a manual computerized search was performed in the bibliographic databases using as keywords "Emergency Department", "Overcrowding", "Emergency Room", "Emergency Service", "Emergency Unit"",Emergency Ward", "Emergency Outpatient Unit", "Emergency Hospital", "Crowding", "Mass Gathering", "Management" and "Comprehensive Health Care". Two independent reviewers analyzed abstracts, titles and full text articles for admissibility, according to the selected inclusion and exclusion criteria.Results: The process lead to include 19 articles. It was possible to group the solutions proposed in five categories: work organization, investment in primary care, creation of new dedicated professional figures, work and structural modifications and implementation of predictive simulation models using mathematical algorithms.Conclusion: The most effective measures to guarantee an improvement in the flow of patients are represented by both improving the efficiency of human resources and by developing predictive mathematical models, regardless of the type of hospital and its location. Considering the complexity of EDs and the multiple characteristics of overcrowding and that the causes of crowding are different and site-specific, a careful examination of the specifics of each ED is necessary to identify improving fields.Keywords: patients flow management, human resource efficiency, predictive mathematical models, patients overload, overflowing